CARDIOVASCULAR RISK SCREENING SERVICES IN SUDANESE COMMUNITY PHARMACIES - SUMIA S MOHAMED; DALIA A BALLAL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objective of this study was to investigate the Sudanese community pharmacists’ knowledge and practice of cardiovascular disease risk assessment services. Methods: The study was conducted as a non-interventional, descriptive, cross sectional community-pharmacy based survey. Results: The Response rate was 91%. The obese and the elderly received the highest ratings for cardiovascular disease risk assessment. Hypertension, type 1 and type 2 diabetes mellitus and ages >55 and 36-55 years were mostly targeted for screening. Variable responses were reported regarding the type of fasting lipid profile that is screened. One third of the participants claimed to have screening evaluation forms. Most participants had the appropriate equipment for screening but only a few had cholesterol measures. Only 27% reported the use of cardiovascular risk charts or calculator for the evaluation. Overwhelming majority had no documentation records and the most available reference was the BNF. Conclusion: The current knowledge and practice of cardiovascular disease risk assessment is poor and need fundamental development. Community pharmacy practice in the Sudan is still product oriented. These services were provided by respondents on voluntary bases without full knowledge or appropriate training on proper assessment and evaluation of the risks that they measured. This needs to change if pharmacy’s potential is to be reached. Collaboration between health authorities and universities is essential to acknowledge the new roles of the pharmacist and provide the appropriate knowledge and training needed to promote and implement the change process that is required.